How to Govern the Confidence Machine? - de Filippi, Primavera; Mannan, Morshed; Reijers, Wessel (Regulation & Governance)
ABSTRACT Emerging technologies pose many new challenges for regulation and governance on a global scale. With the advent of distributed communication networks like the Internet and decentralized ledger technologies like blockchain, new platforms emerged, disrupting existing power dynamics and bringing about new claims of sovereignty from the private sector. This special issue addresses a gap in the literature by focusing the discourse on the issue of trust and confidence in the digital realm. In particular, looking at the evolution of the web (from Web 1.0, to Web 2.0, and then Web 3), this article analyses how every iteration reflects a different way of dealing with the problem of trust online, resulting in a different regulation and governance landscape. Technology is often regarded as a new lever of regulation, attempting to resolve the problem of “trust” online, either through the introduction of a new trusted authority (Web 2.0) or through the introduction of technological guarantees that provide more assurance—or “confidence”—in the way interactions can be operationalized (Web 3). Yet, each of these technologies also introduce new risks and governance costs, ultimately shifting the problem of trust in a new direction rather than resolving it or removing the need for trust altogether. The main contribution of the articles in this special issue is providing a better understanding of the trust challenges faced and posed by emerging technologies and demonstrating how they affect institutional governance—in both theory and practice—with a view to help policymakers find appropriate answers to these challenges.

Hybrid Decision Support in Product Creation - Improving performance with data science and artificial intelligence - Gräßler, Iris; Pottebaum, Jens; Nyhuis, Peter; Stark, Rainer; Thoben, Klaus-Dieter; Wiederkehr, Petra (Industry 4.0 Science)
Technical systems are characterized by increasing interdisciplinarity, complexity and networking. A product and its corresponding production systems require interdisciplinary multi-objective optimization. Sustainability and recyclability demands increase said complexity. The efficiency of previously established engineering methods is reaching its limits, which can only be overcome by systematic integration of extreme data. The aim of "hybrid decision support" is as follows: Data science and artificial intelligence should be used to supplement human capabilities in conjunction with existing heuristics, methods, modeling and simulation to increase the efficiency of product creation.
Keywords: AI; artificial intelligence; Data Science; decision support; extreme data; Künstliche Intelligenz; product creation; product development

Hydrogen economy development in the European Union - Genovese, Matteo; Piraino, Francesco; Corigliano, Orlando; Schlüter, Alexander; Scionti, Eugenio; Fragiacomo, Petronilla (Accelerating the Transition to a Hydrogen Economy)

I(ra)nconsistencies: Novel Insights into Iran’s Censorship - Lange, Felix; Niere, Niklas; von Niessen, Jonathan; Suermann, Dennis; Heitmann, Nico; Somorovsky, Juraj (Proceedings on Privacy Enhancing Technologies)
Iran employs one of the most prominent Internet censors in the world. An important part of Iran’s censorship apparatus is its analysis of unencrypted protocols such as HTTP and DNS. During routine evaluations of Iran’s HTTP and DNS censorship, we noticed several properties we believe to be unknown today. For instance, we found injections of correct static IPs for some domains such as google.com on the DNS level, unclear HTTP version parsing, and correlations between DNS and HTTP censorship. In this paper, we present our findings to the community and discuss possible takeaways for affected people and the censorship circumvention community. As some of our findings left us bewildered, we hope to ignite a discussion about Iran’s censorship behavior. We aim to use the discussion of our work to execute a thorough analysis and explanation of Iran’s censorship behavior in the future.

Igniting Knowledge Management for Assistance Systems in Maintenance: A Method for Knowledge Gathering - Skolik, Alexander Marcus; zur Heiden, Philipp; Donner, Johannes Aurelius Tamino; Priefer, Jennifer (ECIS 2025 Proceedings)

Ihre Waffe war der Zeichenstift. Vorstellung der durch den DAB geförderten Arbeit „Die junge Käthe Kollwitz in ihrer künstlerischen Findungsphase" - Schreckenberg, Carolin (Deutscher Akademikerinnenbund e.V.-Newsletter Juni)

Im Todeswasser: Eine Metapher in der Hebräischen Bibel und im Werbespot ‚Der Weg‘ - Bergmann, Claudia Dorit (Weihnachts-Werbespots als moderne Krippenspiele)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Immersive Smart Home Planning and Automation with Mixed Reality and Digital Twin Technologies - Yigitbas, Enes; Karch, Julian (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Impact of felt obligation and perceived mutual reciprocity on support between mothers and their adult children - Schoenert, Kathrin; Sommer, Sabrina; Buhl, Heike M. (Frontiers in Developmental Psychology)

Impact of non-rotationally symmetric joint orientation on neighbouring joints and component performance in lap shear specimens - Devulapally, Deekshith Reddy; Steinfelder, Christian; Tröster, Thomas; Brosius, Alexander (MATEC Web of Conferences)
This paper discusses the influence of joint orientation with non-rotationally symmetric geometry, on load distribution and structural behavior. The focus is on understanding how changes in the alignment of individual joints affect the distribution of load, neighboring joints, and the overall performance of the component. Lap shear specimens with multiple joints arranged in a line are analyzed to explore these effects. Simplified models are used to model the joints in finite element simulations, allowing for efficient yet accurate analysis of the load distribution and structural response under varying joint orientations. Variations in joint orientation result in measurable changes in the distribution of forces on adjacent joints, influencing their behavior and that of the overall assembly. Experimental validation confirms the numerical results, providing deeper insights into the interaction between individual joints and their surroundings. This work contributes to the development of systematic approaches for optimizing the design of components with non-rotationally symmetric joints. The study highlights the importance of considering directional properties of joints in designing structural components.

Impact of the parameter distribution on the predictive quality of metamodels for clinch joint properties - Einwag, Jonathan-Markus; Mayer, Yannik; Goetz, Stefan; Wartzack, Sandro (Materials Research Proceedings)
Abstract. The growing significance of lightweight design, reveals drawbacks of conventional joining processes such as welding, which are known to consume a considerable amount of energy. This fosters the use of mechanical joining processes including clinching. However, the lack of universally applicable design methods results in a cost- and time-intensive design process. The utilization of machine learning methods can overcome these drawbacks. To ensure a reliable clinch joint design, inherent uncertainties of the design parameter such as tool deviations need to be considered in the design process. Varying distributions of design parameters, due to changes in the manufacturing process, can lead to high-computational effort in recalculating the resulting clinch joint properties with numerical simulations. Current metamodel-based methods for consideration of inherent uncertainties within the design parameters do not investigate the transferability of metamodels to different distributions of design parameters, which can lead to incorrect predictions. Therefore, this contribution investigates the performance of several metamodels on differently distributed design parameters. The obtained results indicate that metamodels demonstrate the best performance when training and evaluation distributions are identical and that polynomial regression models perform best on disparate distributions, when trained on uniform distributions.

Implementation and Results of a Multi-Stage Model Predictive Traffic Light Control System - Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (2024 IEEE 27th International Conference on Intelligent Transportation Systems (ITSC))

Improvement of Wind Power Utilization Through Flexible Operation of Data Center in Wind Parks - Ahmadi, Mehdi; Knorr, Lukas; Meschede, Henning (Renewable Energy)

Impulse 7. Texte und Bilder zur Kunstvermittlung. Ein interdisziplinäres Projekt zur Biennale Venedig 2024.

In Likes We Trust oder die unmögliche Möglichkeit vom Like als Gabe zu sprechen - Schulz, Christian (Populäre Artikulationen – Artikulationen des Populären)

In situ computed tomography – Analysis of settling effects during single-lap shear tests with clinch points - Köhler, D.; Troschitz, J; Kupfer, R.; Gude, M. (Materials Research Proceedings)
Abstract. In the field of mechanical engineering, destructive tests such as shear tests of mechanical joints are usually followed by imaging methods such as microsectioning or computed tomography (CT). They can help to interpret the measured load-displacement curves, analyze the failure behavior and validate numerical models. However, due to unloading, springback effects and crack closures can occur, which influence the state of the investigated specimen. In this context, in situ CT is able to explore the testing process with a specimen under load avoiding these influences. For in situ CT investigations, the displacement increase is interrupted at certain stop points. While the displacement is kept constant, the CT scan is performed. However, it was observed that the reaction force reduces during CT scanning, e. g. due to settling effects in the test setup. Although in situ CT is established now in research, little attention is paid to the uncertainties which arise from the discontinuous testing procedure. This study systematically explores the impact of these interruptions on the load-displacement behavior and the geometry of clinch points during tensile shear testing. To quantify the influence of the interruptions, loads at defined displacement levels and the final geometry are evaluated statistically. We found, that the load-displacement behavior of both test groups is similar. Despite some small but significant statistical deviations of the loads and the final geometry, our results show that, discontinuous testing has a high level of significance for the phenomena overserved in shear tests with clinch points.

Incentive-Based Platoon Formation: Optimizing the Personal Benefit for Drivers - Heinovski, Julian; Ergenç, Doǧanalp; Thommes, Kirsten; Dressler, Falko (IEEE Open Journal of Intelligent Transportation Systems)

Increasing the sensitivity of ultrasonic transmission measurements for elastic material parameter estimation - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Claes, Leander; Birk, Carolin; Henning, Bernd (Measurement Science and Technology)
Abstract Ultrasonic transmission measurements can be used for material characterization, as the propagation time of sound waves and thus their velocity depends on the elastic material parameters. Measurement results for the elastic material parameters are acquired non-destructively using ultrasonic transmission measurements of hollow cylindrical polymer specimens. To determine the material parameters, an inverse approach is used comparing measurements with simulated data. Previous studies show that the procedure exhibits low sensitivity with respect to the shear parameters of the material. In order to increase the sensitivity, we propose to apply a spatially annular excitation on the base of the specimen. As a measure to analyse the sensitivities with respect to all parameters and their linear independence, we observe the volume of the parallelotope of the sensitivity vectors. Here, a scaled boundary finite element formulation of wave propagation in the specimen is expanded to yield derivative information directly, and a sensitivity analysis can be carried out efficiently. Finally, the results of this sensitivity analysis with regard to the annular excitation are also applied to the measurement setup.
Keywords: Sensitivity analysis; Ultrasonic transducer; Guided waves; Polymers; Gram determinant

Influence de l'utilisation de la réalité augmentée lors des expériences chimiques sur la connexion des niveaux de représentation dans les explications des élèves - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Actes des XIIIe Rencontres scientifiques de l’ARDIST)